General Music Education in a Multi-Ethnic Context, on the Example of State-Run Schools in Poland between the World Wars - Jeż Agnieszka (Musicology Today, 2022)
The paper concerns the presence and ideological identity-building function of Polish folk music in Polish state-run schools between the World Wars, and the experiences of Jewish children and teenagers in this regard. The young Polish state brought together populations from the former three partitioned territories, which included numerous national minorities. The need for bond-forming, powerfully symbolic elements supporting a collectively developed national identity was soon strongly felt. Polish folk music, with particular emphasis on its regional varieties, perfectly fitted into the ideological current of patriotic and civic youth education in both state-run and private schools. Dances and songs which children learned at music and PE lessons familiarised them with the wealth of traditions, imbuing them with pride and the love of national culture. The paper quotes examples of young Jews’ experiences in this context, as they encountered Polish folksongs and dances in state-run schools: their responses to this issue and the impact of such contacts on their identities. The source material comes from pre-WWII press, in which we hear the voices of the children themselves, reporting their experiences.